The Political Economy of East Asia - Cai, K. author. aut Link
XII, 261 p.
Keywords: In a systematic study of the political economy of East Asia, Cai adopts an historical perspective alongside a contemporary focus, exploring East Asia's development since the late 19th century. Following similar paths to economic development, East Asian states have achieved economic success, integrating themselves into a regional economy.